2021
DOI: 10.3390/antiox10081298
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Immunoassay for Malondialdehyde-Conjugated Low-Density Lipoprotein Measures Dynamic Changes in the Blood of Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Oxidized low-density lipoproteins play an important role in tissue pathology. In this study, we report a sensitive novel enzyme-linked immunosorbent assay for the detection of malondialdehyde-modified low-density lipoprotein (MDA-LDL), a key component of oxidized LDL. The assay is capable of measuring a variable presence of MDA-LDL within human plasma and serum. We demonstrate the robust nature of the assay on samples stored for over 20 months, as well as high inter-operator reproducibility (r = 0.74, p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Consequently, there is consumption of the circulating anti-oxLDL antibodies as they beneficially clear the increased antigenic load, forming complexes and trafficking them to the reticuloendothelial system for removal in a homeostatic clearance mechanism. These observations are consistent with other studies from our laboratory, which demonstrate acute reduction in anti-MDA-LDL antibodies following major vascular surgery and coronary artery bypass grafting ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, there is consumption of the circulating anti-oxLDL antibodies as they beneficially clear the increased antigenic load, forming complexes and trafficking them to the reticuloendothelial system for removal in a homeostatic clearance mechanism. These observations are consistent with other studies from our laboratory, which demonstrate acute reduction in anti-MDA-LDL antibodies following major vascular surgery and coronary artery bypass grafting ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…We have recently shown that major cardiac surgery with coronary artery bypass grafting results in a depletion of both IgG and IgM anti-MDA-LDL antibodies in tandem with an increase in MDA-LDL levels [ 18 ]. In other earlier studies, transient increases in plasma oxidized LDL and reduction in plasma anti-MDA-LDL antibodies have been identified following percutaneous coronary intervention, albeit over a shorter time course [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sandwich ELISA protocols were established to measure the majority of components within our study. MDA-LDL was measured using LO1 (10 μg/mL) as the capture antibody for MDA-LDL [ 18 ], whilst polyclonal goat anti-human anti-ApoB (Abcam, Cambridge, MA, USA; 1:2000 dilution) was used as the capture antibody for ApoB. A biotinylated anti-ApoB antibody (Abcam, Cambridge, MA, USA; 1:2000), followed by horseradish peroxidase (HRP)-conjugated streptavidin (R&D Systems, Minneapolis, MN, USA; 1:200) were used for detection of both MDA-LDL and ApoB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation